42 The extrahospital use of succinhylcholine produces hyperkalemia?. (26th April 2019) - Jimenez, L; Sanchez, C; Castillo, M; Torres, E; Escudero, C; Hortelano, J
Abstract : Background: Succinhylcholine is a depolarizing relaxant that can cause hyperkalemia. Some clinical studies have shown serious hyperkalemia cases subsequent to the administration of succinhylcholine, reason why many Outpatient Services have withdrawn succinhylcoline from their therapeutic arsenal, and therefore the possibility to perform a Rapid Sequence Intubation (RSI). Method: Our hypothesis is that succinhylcholine, when used as a unique dose in RSI, can cause mild hyperkalemia, as observed in a retrospective observational study of SAMUR-PC assisted cases in 2017. This study includes patients above 18. RSI had been performed in all cases - regardless of their pathologies, and pothasium levels had been measured before and after the administration of succinhylcholine. Results: This study includes patients above 18. RSI had been performed in all cases - regardless of their pathologies, and pothasium levels had been measured before and after the administration of succinhylcholine. A sample size (n) was obtained in 95 cases. The average pothasium before RSI was 4. 0049 with a standard deviation of 0. 9022 while the average pothasium level after RSI was 4.0758 with a standard deviation of 0. 7807. In order to compare the mid-range of both tests and determine significant differences, we performed the Wilconson T test, which shows that there is no statistical significance between the pothasium averages before and after the administration of succinhylcholine. Conclusion: It is therefore confirmed for the first time in the outpatient environment that there is no significant increase of pothasium levels. References: Procedures manual of SAMUR-PC. www.reanimacion.net.Succinylcholine intense debate about its contraindications. www.medicineintensive.org. prevalence of Succinylcholine in intensive care units. Conflict of interest: None. Funding: None.